The positive expression of genotype VII Newcastle disease virus (Malaysian isolate) in Japanese quails (Coturnix coturnix japonica) - Mazlan, Lizma Felisha; Bachek, Noor Farhana; Mahamud, Siti Nor Azizah; Idris, Lokman Hakim; Tan, Sheau Wei; Omar, Abdul Rahman; Mohd Noor, Mohd Hezmee (Veterinary World, 2017)
Aim: Genotype VII Newcastle disease virus (NDV) is the most predominant NDV strains that circulating in Malaysia; thus, this study was aimed to determine the susceptibility of Japanese quails toward genotype VII NDV. Clinical signs, gross pathological lesions of organs, positive detection of virus in organs and cloacal swabs, as well as the expression of the antibody titer, were used as parameters to assess the susceptibility of Japanese quails following infection of genotype VII NDV. Materials and Methods: About 20 quails were divided into three groups (n=8 for Groups A and B; n=4 for the control group). The quails in the Groups A and B were infected via intraocular route with 0.03 ml of 103.5 ELD50 and 107.0 ELD50 of NDV strain IBS 002, respectively, while the control group received 1x phosphate-buffered saline. Cloacal swabs and necropsy were taken on day 7 post-infection for all quails were subjected to one-step reverse transcription real-time quantitative polymerase chain reaction (RT-qPCR) for detection of virus and examination for gross pathological lesion, respectively. Blood serums of infected quails were taken on day 10, 14, and 21 post-day infections and were subjected for hemagglutination inhibition (HI) assay. Results: Depression and ruffled feathers, trachea rales, leg paralysis, and torticollis were shown in some of the quails in both infected groups. Based on statistical analysis, there was no significant difference (p>0.05) in clinical signs between the infected groups. The results for RT-qPCR were found to be negative for all groups, and no gross pathological lesions of organs observed for quails in both infected groups. Trachea, proventriculus, and cecal tonsil were taken for the detection of NDV by RT-qPCR, and some of the organ samples showed positive detection of virus in both infected groups. HI assay showed an increase in mean titers of antibody across time and between infected groups. Conclusion: In summary, Japanese quails are susceptible to genotype VII NDV based on parameters assessed.